ChemInform Abstract: MgO/CoFeB/Ta/CoFeB/MgO Recording Structure with Low Intrinsic Critical Current and High Thermal Stability. Issue 3 (January 2015) - Sato, H.; Yamanouchi, M.; Ikeda, S.; Fukami, S.; Matsukura, F.; Ohno, H.
Abstract Review: 36 refs.